Trajectories and Modes of Autocratization in the Early 21st Century - Cassani, Andrea; Tomini, Luca (PARTECIPAZIONE E CONFLITTO, 2020)
Contemporary processes of autocratization attract growing attention, but their trajectories and modes remain relatively understudied. To contribute filling this gap, we offer one of the first case-oriented comparative analyses of twenty-first century autocratization. First, we examine a global set of cases. Hence, we focus on four typical cases from different regions – namely, Ecuador, Moldova, Thailand and Rwanda – representing different forms of contemporary autocratization. The analysis confirms that autocratization is an empirically relevant phenomenon in this historical phase. Moreover, an evolution is occurring in how this political syndrome unfolds, in the regimes it tends to hit, and in its outcomes. More specifically, the main threat that liberal democracies currently face is a process of sequential autocratization, perpetrated by elected rulers wishing to expand and prolong their power through the loosening of the mechanisms of horizontal accountability and the manipulation of the electoral process. However, we also highlight that an ongoing process of autocratization could be interrupted or reversed.